Mice lacking the conserved transcription factor Grainyhead-like 3 (Grhl3) display increased apposition of the frontal and parietal bones during embryonic development. Issue 1 (December 2016) - Goldie, Stephen; Arhatari, Benedicta; Anderson, Peter; Auden, Alana; Partridge, Darren; Jane, Stephen; Dworkin, Sebastian
Abstract Background Increased apposition of the frontal and parietal bones of the skull during embryogenesis may be a risk factor for the subsequent development of premature skull fusion, or craniosynostosis. Human craniosynostosis is a prevalent, and often serious embryological and neonatal pathology. Other than known mutations in a small number of contributing genes, the aetiology of craniosynostosis is largely unknown. Therefore, the identification of novel genes which contribute to normal skull patterning, morphology and premature suture apposition is imperative, in order to fully understand the genetic regulation of cranial development. Results Using advanced imaging techniques and quantitative measurement, we show that genetic deletion of the highly-conserved transcription factorGrainyhead-like 3 (Grhl3 ) in mice (Grhl3 −/− ) leads to decreased skull size, aberrant skull morphology and premature apposition of the coronal sutures during embryogenesis. Furthermore, Grhl3 −/− mice also present with premature collagen deposition and osteoblast alignment at the sutures, and the physical interaction between the developing skull, and outermost covering of the brain (the dura mater), as well as the overlying dermis and subcutaneous tissue, appears compromised in embryos lackingGrhl3 . AlthoughGrhl3 −/− mice die at birth, we investigated skull morphology and size in adult animals lacking oneGrhl3 allele (heterozygous;Grhl3 +/− ), which are viable and fertile. We found that these adult mice also present with a smaller cranial cavity, suggestive of post-natal haploinsufficiency in the context of cranial development. Conclusions Our findings show that our Grhl3 mice present with increased apposition of the frontal and parietal bones, suggesting thatGrhl3 may be involved in the developmental pathogenesis of craniosynostosis.